Avaliação da influência da periodontite experimental sobre os tecidos periodontais e da região peninana de ratos - Pedrotti, Stefany (2015)
Periodontal disease is characterized by a chronic infection, which may cause systemic inflammation due to high levels of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-18 (IL-18), contributing to the development of endothelial dysfunction in various organs. The impairment of endothelial function can lead to erectile dysfunction, because it is characterized by vascular changes such as occlusion of cavernous arteries by atherosclerosis and reduction vascular reactivity due to decreased release of nitric oxide. In this sense, inflammation associated with periodontal disease may damage the penile endothelial layer, leading to occurrence of erectile dysfunctional. However, the potential role of chronic periodontitis in the pathophysiology of erectile dysfunction remains scarce. Therefore, the aim of the study was to evaluate the tissue morphology of periodontal and penis rats associated or not with experimentally induced periodontitis. For this, 18 Wistar rats were obtained and induced periodontal disease in 9 rats, whereas the remaining 9 rats served as controls. After 30 days of induction of periodontal disease, the sexual behavior of rats was recorded and later, the animals were sacrificed to obtain gingival sample, hemimandible and penis to the morphological analysis, morphometric, immunological and radiographic. The results showed that experimental periodontitis contributed to the reduction in the sexual behavior of rats (p<0.05) and caused alveolar bone loss with a significant increase in osteoclastic activity and gingival volume (p<0.05). Moreover, the group with periodontitis had a higher concentration of inflammatory cytokines such as IL-6 in the gingiva and TNF-α in the penis (p<0.05). There was no statistically significant difference in ventral-dorsal and side-to-side distance of the penis (p> 0.05), however there was a higher thickness and a shorter area statistically significant of penile dorsal artery in the group with experimental periodontitis, as well as a smaller area of vascular spaces of the penile cavernous tissue (p<0.05). Based on these results, it is concluded that the experimental periodontitis caused structural and functional changes in the penis Wistar rats and sexual behavior changes, therefore systemic inflammation caused by periodontal disease can be an important risk factor for erectile dysfunction, that is why is necessary the development of interventions involving many health professionals for prevention and treatment of these two diseases that endanger the health and general well-being of individuals